Analisis Impregnasi Nanopartikel Tembaga (Cu) Pada Non Woven Polypropylene - Musfirah Cahya F.T (Institut Sains dan Teknologi Nasional, 2023)
Abstract To determine the density with copper nanoparticles and the addition of mass of polypropylene non-woven fabric and the characteristics of the crystal structure of the formed copper nanoparticles. Synthetic copper nanoparticles using substances which is precursor of copper from copper sulfate pentahydrate (CuSO4.5H2O), ascorbate acid (C6H8O6) as an antioxidant, and reductor solution using sodium borohydrate (NaBH4). The ex-situ formation of copper nanoparticles was then impregnated on non-woven polypropylene through an immersion process with different variations of time. Based on characterization of X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), and Scanning Electron Microscope (SEM), formed copper nanoparticles characterized of face centered cubic with high increasing of crystalinity at [1, 1, 1] with average size is 65 nm and the wavelength showed at the peak of 730 cm-1 and 710 cm-1 identified as copper nanoparticles. The addition of the highest density in the sample is 5.37%.. Keywords: Copper, Crystal Structure ,Density, Nanoparticle.